Becoming professional translators: Developing effective TAP course for undergraduate students - Rudy Sofyan; Bahagia Tarigan (Indonesian Journal of Applied Linguistics, 2023)
The Translation as a Profession (TAP) course, offered in a translation study program at a state university in Sumatra, Indonesia, is designed to prepare its future graduates to become not only translation scholars but also professional translators and entrepreneurs in the translation field. Therefore, it requires a well-organized program and carefully selected learning materials. Previous studies regarding TAP course development have yet to explore how learning materials would prepare students to be professional translators. Thus, this study aims to explore further how the TAP materials help student translators become professional translators. This descriptive study used both primary and secondary data. The primary data were collected using questionnaires and in-depth interviews with eight translation scholars and seven professional translators. The secondary data were documents. The questionnaire data were analyzed with a Likert scale; meanwhile, the interview and document with an interactive model. The results revealed five topics that systematically helped student translators to become professional translators. The topics are helpful because they provide students with skills (theoretical, practical, technological skills) needed in current professional translation practices. In addition, the topics also emphasize practical works in the form of translation internships that can be conducted in several small-scale translation businesses available in the local area.